Home processing of tomatoes (Solanum lycopersicum): effects on in vitro bioaccessibility of total lycopene, phenolics, flavonoids, and antioxidant capacity. (28th January 2014) - Kamiloglu, Senem; Demirci, Melek; Selen, Saniye; Toydemir, Gamze; Boyacioglu, Dilek; Capanoglu, Esra
Abstract BACKGROUND In order to investigate the effect of home processing on the bioaccessibility of health‐related constituents of tomatoes, total lycopene, phenolics, flavonoids and antioxidant capacity were determined from seven different tomato products using an in vitro gastrointestinal digestion model. Additionally, the changes in the contents of the major tomato phenolics were determined and compared for these different tomato products using HPLC. RESULTS The results revealed that paste processing and drying significantly increased the bioaccessible total lycopene content (2.2‐ and 3.8‐fold, respectively), total phenolic content (2.3‐ and 2.0‐fold, respectively), total flavonoid content (9.0‐ and 2.5‐fold, respectively) and total antioxidant capacity (6.3‐ and 8.0‐fold for the DPPH assay, 26‐ and 33‐fold for the CUPRAC assay, respectively) (P < 0.05) compared to fresh tomatoes. HPLC analysis revealed significantly lower (P < 0.05) rutin content in puree and juice. The loss of naringenin chalcone in some tomato products, as well as its conversion into naringenin in heat‐treated products was observed. CONCLUSION The current study provided valuable insights into the changes in the content and bioaccessibility of tomato antioxidants as a result of home processing. © 2013 Society of Chemical Industry